Analisis Faktor-Faktor yang Memengaruhi Penyerapan Tenaga Kerja pada Sub Sektor Hotel di Kabupaten/Kota Provinsi Bali (2014 - 2024) - Hendrikus Budu,; I Wayan Sukadana, (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The tourism sector is a leading sector that plays a strategic role in the economic development of Bali Province, both in increasing Gross Regional Domestic Product (GRDP) and in generating employment opportunities. Bali’s economic dependence on tourism causes the dynamics of this sector to strongly influence employment conditions, particularly in the periods before, during, and after the COVID-19 pandemic. Therefore, it is important to analyze the factors influencing employment absorption in the tourism sector in Bali Province. This study aims to analyze the effect of GRDP, the number of tourist visits, and the number of hotels on employment absorption in the tourism sector in Bali Province during the 2014–2024 period. This research employs panel data consisting of a combination of time series data over 11 years and cross-sectional data from nine regencies/cities in Bali Province, resulting in 99 observations. The analytical method used is panel data regression with simultaneous testing (F-test) and partial testing (t-test). The results indicate that simultaneously the variables of GRDP, the number of tourist visits, and the number of hotels have a significant effect on employment absorption in the tourism sector in Bali Province. Partially, GRDP and the number of tourist visits have a positive and significant effect, while the number of hotels has a positive but not significant effect on employment absorption.